Analisis Kesulitan Belajar Siswa pada Pembelajaran Tatap Muka Terbatas Selama Pandemi Covid 19 - Nasution, Saidatunnisa; Simanjuntak, Lia Angraini; Sitanggang, Winanta; Tambunan, Jenita br. (CV. Creative Tugu Pena, 2022)
Covid-19 pandemic has affected all sectors of life in Indonesia, including the education sector. Now, learning that was originally done online has turned into limited face-to-face learning. During the process of applying face-to-face learning, there are limited learning difficulties for students. The purpose of this study was to determine student learning difficulties with face-to-face learning (PTM) limited during the Covid-19 pandemic. The research method used descriptive qualitative with research subjects 30 students at MTsN 2 Medan. The results of this study showed that there were several difficulties faced by students in implementing limited online learning during the Covid-19 pandemic at MTS Negeri 2 Medan, including aspects of Student Learning Motivation (78%) aspects of Student Activity (70%), Facilities Infrastructure (76.6%), Teacher (59.2%) and Student Barriers (62.8%). Even so, Online Learning is seen as the most effective learning compared to the online system carried out during the Covid-19 pandemic. Hence, there needs to be cooperation from all parties, especially in developing teacher human resources in teaching so that Limited online learning can be carried out well, so students can learn well. Keywords: Student Difficulty Learning, Online Learning, Limited Onlinie Learning